2023
DOI: 10.1093/braincomms/fcad019
|View full text |Cite
|
Sign up to set email alerts
|

Decreased myelin proteins in brain donors exposed to football-related repetitive head impacts

Abstract: American football players and other individuals exposed to repetitive head impacts can exhibit a constellation of later-life cognitive and neuropsychiatric symptoms. While tau-based diseases such as chronic traumatic encephalopathy can underpin certain symptoms, contributions from non-tau pathologies from repetitive head impacts are increasingly recognized. We examined cross-sectional associations between myelin integrity using immunoassays for myelin-associated glycoprotein and proteolipid protein 1 with risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…In addition, a single nuclear RNA sequencing study found that the number of oligodendrocytes was reduced and altered in relative subtype proportions in the dorsolateral frontal white matter of older athletes with CTE compared with controls. A recent autopsy study of 205 older male brain donors with and without CTE found decreased myelin-associated proteins in frontal white matter that corresponded to years of exposure and age at first exposure to American football. Using high spatial resolution ex vivo diffusion tensor imaging, researchers have reported alterations in fractional anisotropy in white matter underlying sulci with CTE lesions and microscopic evidence of axonal disruption .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a single nuclear RNA sequencing study found that the number of oligodendrocytes was reduced and altered in relative subtype proportions in the dorsolateral frontal white matter of older athletes with CTE compared with controls. A recent autopsy study of 205 older male brain donors with and without CTE found decreased myelin-associated proteins in frontal white matter that corresponded to years of exposure and age at first exposure to American football. Using high spatial resolution ex vivo diffusion tensor imaging, researchers have reported alterations in fractional anisotropy in white matter underlying sulci with CTE lesions and microscopic evidence of axonal disruption .…”
Section: Discussionmentioning
confidence: 99%
“…White matter rarefaction was increased in the deceased young athletes with CTE, albeit of marginal significance. White matter changes are also common in older individuals with autopsy-confirmed CTE . White matter rarefaction in older brain donors with CTE is directly associated with RHI exposure, CTE status, and dementia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These may include environmental factors previously linked to dementia such as depression, air pollution, physical inactivity, diabetes, hypertension, hearing loss, obesity, excessive alcohol consumption, lack of social contact, and insomnia 44,45 . Nontraditional and new measures of pathology such as white matter integrity, synaptic density, and neuroinflammatory measures may mediate some of these effects and require further study 46,47 …”
Section: Discussionmentioning
confidence: 99%
“…44,45 Nontraditional and new measures of pathology such as white matter integrity, synaptic density, and neuroinflammatory measures may mediate some of these effects and require further study. 46,47…”
Section: Importance Of Factors Beyond Known Pathologiesmentioning
confidence: 99%